Rapid carbon accumulation in a peatland following Late Holocene tephra deposition, New Zealand. (15th October 2020) - Ratcliffe, Joshua L.; Lowe, David J.; Schipper, Louis A.; Gehrels, Maria J.; French, Amanda D.; Campbell, David I.
Abstract: Contemporary measurements of carbon (C) accumulation rates in peatlands around the world often show the C sink to be stronger on average than at times in the past. Alteration of global nutrient cycles could be contributing to elevated carbon accumulation in the present day. Here we examine the effect of volcanic inputs of nutrients on peatland C accumulation in Moanatuatua Bog, New Zealand, by examining a high-resolution Late Holocene C accumulation record during which powerful volcanic eruptions occurred, depositing two visible rhyolitic tephra layers (Taupo, 232 ± 10 CE; Kaharoa, 1314 ± 12 CE). Carbon accumulation rates since c. 50 CE, well before any human presence, increased from a background rate of 23 g C m −2 yr −1 up to 110 g C m −2 yr −1 following the deposition of the Taupo Tephra, and 84 g C m −2 yr −1 following the deposition of the Kaharoa Tephra. Smaller but nevertheless marked increases in C accumulation additionally occurred in association with the deposition of three andesitic-dacitic cryptotephras (each ≤ ∼1 mm thick) of the Tufa Trig Formation between the Taupo and Kaharoa events. These five periods of elevated C uptake, especially those associated with the relatively thick Taupo and Kaharoa tephras, were accompanied by shifts in nutrient stoichiometry, indicating that there was greater availability of phosphorus (P) relative to nitrogen (N) and C during the period of high C uptake. Such P was almost certainly derived from volcanic sources, with P being present in the volcanic glass at Moanatuatua, and many of the eruptions described being associated with the local deposition of the P rich mineral apatite. We found peatland C accumulation to be tightly coupled to N and P accumulation, suggesting nutrient inputs exert a strong control on rates of peat accumulation. Nutrient stoichiometry indicated a strong ability to recover P within the ecosystem, with C:P ratios being higher than most other peatlands in the literature. We conclude that nutrient inputs, deriving from volcanic eruptions, have been very important for C accumulation rates in the past. Therefore, the elevated nutrient inputs occurring in the present day could offer a more plausible explanation, as opposed to a climatic component, for observed high contemporary C accumulation in New Zealand peatlands. Graphical abstract: Image 1 Highlights: Peatland carbon accumulation rates (CAR) greatly increased during periods of tephra input. Nutrient stoichiometry suggests greater phosphorus abundance during periods of high CAR associated with tephra deposition. P potentially derives from aerosols as well as from dissolution of freshly-deposited glass and apatite. Nutrient stoichiometry suggests C accumulation is tightly coupled to P inputs. P inputs appear to exert a strong control on C dynamics in the peatland studied as well others in the literature.